2019
DOI: 10.1371/journal.pone.0208287
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity to Hsp90 inhibitors of both normal and oncogenically transformed cells is determined by the equilibrium between cellular quiescence and activity

Abstract: The molecular chaperone Hsp90 is an essential and highly abundant central node in the interactome of eukaryotic cells. Many of its large number of client proteins are relevant to cancer. A hallmark of Hsp90-dependent proteins is that their accumulation is compromised by Hsp90 inhibitors. Combined with the anecdotal observation that cancer cells may be more sensitive to Hsp90 inhibitors, this has led to clinical trials aiming to develop Hsp90 inhibitors as anti-cancer agents. However, the sensitivity to Hsp90 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 78 publications
0
17
1
Order By: Relevance
“…Cytosolic HSP90, with its large clientele of proteins, is a major network hub in the cellular proteome; as a result, pharmacological inhibition of HSP90 greatly destabilizes the cellular proteome [46][47][48][49][50][51]. This is in stark contrast to what we found for TRAP1, whose loss does not cause a significant imbalance in either the mitochondrial or cellular proteomes.…”
Section: Discussioncontrasting
confidence: 73%
“…Cytosolic HSP90, with its large clientele of proteins, is a major network hub in the cellular proteome; as a result, pharmacological inhibition of HSP90 greatly destabilizes the cellular proteome [46][47][48][49][50][51]. This is in stark contrast to what we found for TRAP1, whose loss does not cause a significant imbalance in either the mitochondrial or cellular proteomes.…”
Section: Discussioncontrasting
confidence: 73%
“…The premise of the use of HSP90 inhibitors in cancer therapy is based on the findings that cancer cells are more sensitive to HSP90in than untransformed normal cells. A recent study implicated cellular quiescence and activity as a likely cause for the differential sensitivity of normal and cancer cells to HSP90in (Echeverria et al, 2019). The cellular activity of cancer cells is driven by proliferation and the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which HSP90 supports tumor proliferation remains ill-defined, but likely involves chaperoning a number of oncogenic drivers (Vartholomaiou et al, 2016). A recent study argued that the active maintenance of the cell cycle in cancer cells makes them more sensitive to an HSP90 inhibitor (hereafter referred to as HSP90in) (Echeverria et al, 2019). Thus, HSP90 represents a key chaperone system that is conserved from bacteria to human, essential for viability in eukaryotes and relevant for evolution and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp90 inhibitors are potent anticancer and anti‐inflammatory compounds. Their actions are due to the fact that exert a prominent ability to sabotage the maturation of a plethora of client proteins, which are both the messengers and the transducers of severe inflammatory responses . Our laboratory, as well as other groups, investigate the potential of those compounds to suppress inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Their actions are due to the fact that exert a prominent ability to sabotage the maturation of a plethora of client proteins, which are both the messengers and the transducers of severe inflammatory responses. [9,10] Our laboratory, as well as other groups, investigate the potential of those compounds to suppress inflammation. We have already demonstrated that those agents induce the expression of P53, which in turn orchestrates a battery of molecular events that result to barrier strengthening.…”
Section: Introductionmentioning
confidence: 99%